The Phonological-Similarity Effect Differentiates Between Two Working Memory Tasks. - MacAndrew, Danean K.; Klatzky, Roberta L.; Fiez, Julie A. (Psychological Science., 2002)
A study was conducted to compare and contrast the phonological processing requirements of the verbal recognition memory tasks that have been used in functional neuroimaging research. Findings revealed the existence of a phonological-similarity effect only in the task that involved sequential presentation and explicit verbal practice.